Women and Inequality in a Changing World Exploring New Paradigms for Peace - Mahmoudi, Hoda; Parpart, Jane L.; Seaman, Kate (Gender in a Global/Local World, 2024)
Women and Inequality in a Changing World explores the obstacles women continue to face to their equal participation in all areas of daily life-political, social, and eco- nomic-which persist despite the growth in the education of girls, large-scale social movements, and political waves. The volume widens and deepens understanding of women in relation to the inequalities they face, based not only on gender, but also on race, class, religion, and more. It also highlights the progress that women have made, and how this progress contributes to the creation of more peaceful and prosperous societies. This interdisciplinary book brings together leading scholars and practitioners from across the globe to provide a wide range of perspectives and experiences, examine crucial questions, and oﬀer new ideas and innovative solutions to increasing the role of women moving forward. This book will be of great interest to students and scholars of gender studies, women's studies, and political science, as well as practitioners working at the intersection of women and global issues. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.